Optimal Battery Energy Storage System Placement Strategy in Central Java Electrical System for Voltage and Losses Improvement - Fikry, Hafizh Al; Samual, Muhammad Gillfran; Sudiarto, Budi (International Journal of Electrical, Computer, and Biomedical Engineering, 2024)
Over the past few decades, advances in energy storage technology, particularly in the form of Battery Energy Storage Systems (BESS), have provided innovative solutions to address various challenges in the power grid such as voltage fluctuations and high levels of losses, which negatively impact the efficiency and quality of electricity provision. BESS has advantages over other energy storage technologies such as having lower costs, faster response times to power equipment or devices, and increased efficiency and flexibility. The purpose of this research is to determine the optimal capacity and location of the placement of BESS to get an improvement in the voltage profile and losses in the Central Java Province power system. In this study, BESS is incorporated into the Jelok substation based on the calculation method under day and night conditions, which will be sought for the most optimal placement. After getting the most optimal placement, the optimal BESS capacity based on the calculation method, 15 MWh, and 25 MWh will be compared. The effect of optimum BESS placement and sizing of up to 0.0035 pu, and reduce losses up to 1.87 MW.